2001
DOI: 10.1021/es010791k
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Air−Water Exchange of Polychlorinated Biphenyls in the New York−New Jersey Harbor Estuary

Abstract: Simultaneous measurements of polychlorinated biphenyls (PCBs) in the air and water over Raritan Bay and New York Harbor were taken in July 1998, allowing the first determinations of air-water exchange fluxes for this heavily impacted system. Average gas-phase concentrations of sigmaPCBs were 1.0 ng m(-3) above Raritan Bay and 3.1 ng m(-3) above New York Harbor. A similar gradient was observed for dissolved water concentrations (1.6 and 3.8 ng L(-1), respectively). Shallow slopes of log K(oc) vs log K(ow) plots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
110
2
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(123 citation statements)
references
References 55 publications
7
110
2
4
Order By: Relevance
“…These results are consistent with those of Butcher et al (1998), which suggests that less than 10% of PCBs containing three or more chlorines are sorbed to colloids in the Hudson River (USA) under normal conditions (4.79 mg/L DOC and 1.40 mg/L POC). These values conflict with the findings of Baker et al (2002) and Totten et al (2001), who have suggested that at commonly encountered DOC and SPM concentrations, substantial fractions of moderately hydrophobic compounds were sorbed to the colloidal phase. It should be noted that the PCB congeners detected in the present study were di-to tetra-chlorobiphenyls, which are less hydrophobic compounds compared to higher chlorinated congeners.…”
Section: The Effect Of Doc and Bccontrasting
confidence: 93%
See 3 more Smart Citations
“…These results are consistent with those of Butcher et al (1998), which suggests that less than 10% of PCBs containing three or more chlorines are sorbed to colloids in the Hudson River (USA) under normal conditions (4.79 mg/L DOC and 1.40 mg/L POC). These values conflict with the findings of Baker et al (2002) and Totten et al (2001), who have suggested that at commonly encountered DOC and SPM concentrations, substantial fractions of moderately hydrophobic compounds were sorbed to the colloidal phase. It should be noted that the PCB congeners detected in the present study were di-to tetra-chlorobiphenyls, which are less hydrophobic compounds compared to higher chlorinated congeners.…”
Section: The Effect Of Doc and Bccontrasting
confidence: 93%
“…It should be noted that the PCB congeners detected in the present study were di-to tetra-chlorobiphenyls, which are less hydrophobic compounds compared to higher chlorinated congeners. In the study by Totten et al (2001), the fractions of tri-and tetra-PCBs sorbed to colloids in the New York/New Jersey Harbor were 6% and 14%, respectively, which was similar to the results in this study. The K OC(obs) values of PCBs were one to two orders of magnitude higher than the values predicted from the empirical organic matter partitioning model for the two yearly campaigns (Fig.…”
Section: The Effect Of Doc and Bcsupporting
confidence: 87%
See 2 more Smart Citations
“…SVOCs in the water column partition into three phases: the truly dissolved phase, the particulate phase and the colloidal organic material (Totten et al, 2001). The truly dissolved and colloidal phases can be categorized as apparent dissolved phase, which refers to the non-filter retained fraction.…”
Section: Theoretical Approachmentioning
confidence: 99%